Community-based aortic stenosis detection: clinical and echocardiographic screening during influenza vaccination - Peter Bramlage; Richard Paul Steeds; Martin Thoenes; Cornelia Deutsch; Andrew Potter; Navjeet Mangat; Maren Fröhlich (Open Heart)
Background Degenerative aortic stenosis (AS), the most common valvular heart disease in the Western world, is often diagnosed late when the mortality risk becomes substantial. We determined the feasibility of AS screening during influenza vaccination at general practitioner (GP) surgeries in the UK.Methods Consecutive subjects aged >65 years presenting to a GP for influenza vaccination underwent heart auscultation and 2D echocardiography (V-scan). Based on these findings, a patient management strategy was determined (referral to cardiologist, review within own practice or no follow-up measures) and status at 3 months was determined.Results 167 patients were enrolled with a mean age of 75 years. On auscultation, a heart murmur was detected in 30 of 167 (18%) patients (6 subjects with an AS-specific and 24 with a non-specific murmur). 75.2% of those with no murmur had a negative V-scan finding. Conversely, 16 of 30 (53%) patients with any murmur had an abnormal V-scan finding that was largely related to the aortic valve. Using clinical auscultation and V-scan screening, a decision not to pursue follow-up measures was taken in 147 (88%) cases, whereas 18 (10.8%) subjects were referred onward; with 5 of 18 (27.8%) and 3 of 18 (16.7%) being diagnosed with mild and moderate AS.Conclusions Our pilot study confirms feasibility of valvular heart disease screening in the elderly in a primary care setting. Using simple and inexpensive diagnostic measures and 7.3 million UK inhabitants undergoing influenza vaccination, nationwide screening could potentially identify 130 000 patients with moderate AS and a significant number of patients with severe AS.